Initial inferior vena cava and aorta diameter parameters measured by ultrasonography or computed tomography does not correlate with vital signs, hemorrhage or shock markers in trauma patients - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN; ONUR, ÖZGE ECMEL (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2017)
BACKGROUND: Ultrasonography (US) is noninvasive, readily available, and cheap. The diameter of inferior vena cava (dIVC) and its respiratory variation were proposed as a good surrogate of the hemodynamic state. However, recent studies have shown conflicting results, and the value of IVC-derived parameters in the estimation of fluid status and hemorrhage remains unclear. METHODS: This was an observational study of trauma patients who presented to emergency department. dIVC and aorta diameter (dAorta) were measured at the initial US and CT in all patients. The correlation of these measurements and all parameters derived from those measurements along with the initial vital signs and laboratory values of hemorrhage (hemoglobin, hematocrit) and shock (lactate, base excess) were assessed. US and CT values were also compared for accuracy using Bland-Altman analysis. RESULTS: The final study population was 140, with a mean age of 38 years and 79.3% were male. dIVC and dAorta did not have any clinically significant correlation with any of the vital signs or laboratory values of hemorrhage or shock when measured by US or CT. A good and significant correlation was observed between dIVC and dAorta measured by US and CT. CONCLUSION: The value of an initial and single measurement of IVC and aorta parameters in the evaluation of trauma patients should be questioned. However, the change in the measured parameters may be of value and should be investigated in further studies.
Keywords: Aorta; aortacaval index; caval index; collapsibility index; diameter; distensibility index; inferior vena cava; shock; trauma; CENTRAL VENOUS-PRESSURE; RIGHT ATRIAL PRESSURE; SONOGRAPHIC MEASUREMENT; HEMODIALYSIS-PATIENTS; NONINVASIVE ESTIMATION; INTRAVASCULAR VOLUME; FLUID STATUS; BLOOD-LOSS; ULTRASOUND; INDEX